Konsep Penawaran Dalam Perspektif Islam - Hafid, Abdul (Departemen Ekonomi Syariah Fakultas Ekonomi dan Bisnis Universitas Airlangga, 2015)
The purpose of this paper is to describe how the concept of Islamic economy in the perspective of supply and what are the factors that influence the supply. Research methods in this paper using the quantitative method with study literature. The results of this paper concludes that in the analysis of Islam, offer maximum efficiency of production will occur if the concept in Islamic economic instruments for selected results than using conventional economic interest in the instrument. So the existence of this new discovery, and discourse, which is much better than the side of the theory or practice will be more assured that the Islamic Economic system is a